The Legal Framework for Joint Development of China’s Onshore Oil Resources: Negotiation Strategies and Future Prospects - Wolf, Kevin M. (Columbia Journal of Asian Law, 1995)
On June 8, 1995, the China National Petroleum Company (“CNPC”) announced a third round of bidding for onshore petroleum exploration and development projects in locations in northwest China. The offering was of potential interest to foreign investors because it included twelve exploration blocks in the Tanm and Junggar Basins, remote areas in Xinjiang that are widely regarded as two of the most prospective yet underexplored oil regions in the world. As a result, on February 5, 1996, Texaco, Inc. and Agip (Overseas) Ltd. jointly signed two petroleum contracts with the CNPC to explore and develop reserves in two exploration blocks located in the Tarim Basin. On March 19, 1996, Esso China Upstream Ltd., a subsidiary of Exxon, also signed two petroleum contracts with the CNPC to explore and develop two additional exploration blocks in the northwestern part of the Tarim Basin.